Review of recent efforts in cooling photovoltaic panels pvs for enhanced performance and better impact on the environment - Hussen Hajjaj, Sami Salama; Ahmad Aqeel, Ahmad Abdul Kareem; Sultan, Mohamed Thariq Hameed; Shahar, Farah Syazwani; Md Shah, Ain Umaira (MDPI, 2022)
The global need for energy has grown in tandem with mankind’s development and spread. This has resulted in an increase in the use of fossil energy sources, a decline in these sources and an increase in pollution, necessitating the search for renewable energy sources. One of the important ways to reduce pollution resulting from the increasing consumption of fossil energy is to enhance the sources of solar energy, of which photovoltaic cells (PV) are one of its most important tools. Therefore, it was necessary to pay attention to improving its efficiency for it to become a promising source of clean energy. PVs turn solar energy into electricity; however, the amount of electricity generated decreases as the temperature of the cells rises in response to the sun’s heat. Cooling of the optical surfaces is one of the most important elements to consider while running solar PV systems to obtain maximum efficiency. The electrical efficiency of PVs is enhanced when suitable cooling technology is used, and the rate of cell breakdown is reduced over time, extending the life of the PV panels. There are many materials used to remove unwanted heat in PV cells, and in recent years, the focus has been on integrating nanomaterials in specific proportions with traditional cooling materials such as water to improve their thermal properties. As a bio-material that is environmentally friendly, renewable, sustainable, inexpensive and has high mechanical properties, cellulose nanocrystals (CNCs) are one of the most promising materials for improving the properties of cooling materials for cooling PV cells and improving their performance.